PARENTAL CONFLICT AND ITS PSYCHOLOGICAL IMPACT ON ADOLESCENT BEHAVIOR (International Conference on Modern Science and Scientific Studies, 2025)
Parental conflict is a widespread issue that significantly affects adolescents’ psychological development and behavior. This paper explores the psychological consequences of ongoing inter-parental conflict, focusing on emotional regulation, mental health, academic engagement, and social relationships. Drawing from major psychological theories and international research, the article emphasizes that chronic exposure to parental discord—whether verbal, emotional, or physical—has detrimental effects on adolescent well-being. Practical recommendations include family-based interventions, school counseling programs, and parent education initiatives.